Fintech in Latin America and the Caribbean : Stocktaking - Berkmen, Pelin; Arze del Granado, Javier; Beaton, Kimberly; Gershenson, Dmitry (Washington, D.C. : International Monetary Fund, 2019)
In Latin America and the Caribbean (LAC), financial technology has been growing rapidly and is on the agenda of many policy makers. Fintech provides opportunities to deepen financial development, competition, innovation, and inclusion in the region but also creates new and only partially understood risks to consumers and the financial system. This paper documents the evolution of fintech in LAC. In particular, the paper focuses on financial development, fintech landscape for domestic and cross border payments and alternative financing, cybersecurity, financial integrity and stability risks, regulatory responses, and considerations for central bank digital currencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet